The Rubaiyat of Omar Khayyam - Fitzgerald, Edward (Wordsworth Editions Ltd, 1993)
This edition presents the classic free translation by Edward Fitzgerald of the great Persian poem( rubaiyat )by the 12th century astronomer and poet - Omar Khayyam.
Keywords: General; Poetry